Why Asia will be unstable but not at war: toward a democratic realist perspective - Peou, Sorpong (Penerbit Universiti Kebangsaan Malaysia, 2023)
This article advances the argument that (Indo-Pacific) Asia as a broad region is likely to experience growing instability because of the ongoing nuclear threat posed by North Korea, territorial disputes among maritime powers, and the rapid rise of China. But the region will not be at war mainly because of the preponderance of collective democratic power.